Inflammation, ER Stress, Autophagy and MCP-1/CCR2 Pathway - Kolattukudy, Pappachan E. (2012)
Numerous inflammatory cytokines have been implicated in the pathogenesis of cardiovascular diseases. Monocyte chemoattractant protein (MCP)-1/CCL2 that is expressed by mainly inflammatory cells and stromal cells such as endothelial cells, and its expression is upregulated following pro-inflammatory stimuli and tissue injury. MCP-1 can function as a traditional chemotactic cytokine and also regulates gene transcription. The recently discovered novel zinc-finger protein, called MCPIP (MCP-1-induced protein), which initiates a series of signaling events that causes oxidative and endoplasmic reticulum (ER) stress, leading to autophagy that can result in cell death or differentiation depending on the cellular context. After briefly reviewing the basic processes involved in inflammation, ER stress and autophagy, the recently elucidated role of MCP-1 and MCPIP in inflammatory diseases is reviewed. MCPIP was found to be able to control inflammatory response by inhibition of NFκB activation via its deubiquitinase activity or by degradation of mRNA encoding a set of inflammatory cytokines via its RNase activity. The potential inclusion of such a novel deubiquitinase in the emerging anti-inflammatory strategies for the treatment of inflammation related diseases such as cardiovascular diseases and type 2 diabetes is briefly discussed.